Pengaruh Ekstrak Air Selada Laut (Ulva Lactuca) Terhadap Berat Badan Pada Tikus Diabetes - Rinawati Rinawati; Lili Eky Nursia N; Sri Wahyuni Muhsin; Siti Maisyaroh Fitri Siregar (STIGMA: Jurnal Matematika dan Ilmu Pengetahuan Alam Unipa, 2020)
Unhealthy lifestyle is one of the leading causes to Diabetes Mellitus (DM) disorder which is characterized by beyond normal limits of high blood glucose levels. Seawed (Ulva lactuca) is one type of natural material that is potentially to be anti-DM. Unfortunately, it is not familiar yet to the wider community, especially in Aceh. The purpose of this study was to determine the effect of giving Ulva lactuca water extract to the body weight of DM rats. The research is an experimental completely randomized design (CRD). Rats were grouped into 5 treatments with three replications, namely: KN = normal control (only fed and distilled water), Ka = STZ control (rat induced STZ 65 mg), P1 = rat DM + extract dose 200 mg / KgBB, P2 = DM rats + extract dose 300 mg / KgBB, P3 = DM rats + extract dose 400 mg / KgBB. Measurement of body weight (BB) of rats was carried out for 28 days. Data analysis was performed statistically (ANOVA). The results showed that the water extract of Ulva lactuca affected the changes in body weight of DM rats. The treatment groups of P1, P2 and P3 gained weight after being given Ulva lactuca water extract. The highest percentage of weight increase was found in the P2 and P3 treatment groups. Keywords: Diabetes Mellitus, Weight, Sea Lettuce (Ulva lactuca)